Study of the Taqrirat al-Sadidah Book to Strengthen the Fiqh Muamalah Literacy of Students at the Attahdzib Islamic Boarding School - Muhammad Ma'rur; Zainal Fanani; Misbachul Munir (LP3M STAI At-Tahdzib Jombang, 2026)
This community service activity aims to strengthen the literacy of fiqh muamalah of students at Attahdzib Islamic Boarding School, Jombang, through the study of the book Taqrirat al-Sadidah Volume 2. The background of this activity is the limited understanding of students regarding the basic principles of economic transactions in accordance with sharia, even though the Islamic boarding school has a book study forum that can be optimally utilized to strengthen this literacy. The mentoring method is implemented through a regular study forum by combining the bandongan method and contextual muamalah discussions, including the preparation stage, implementation of the study, strengthening contextual understanding, reflection-evaluation, and documentation of activities. The results of the mentoring show an increase in students' understanding of the basic concepts of fiqh muamalah such as contracts and transaction justice, an increase in the ability to relate fiqh to the realities of life, active participation in discussions, and a growing awareness of carrying out muamalah in accordance with sharia. This activity also strengthens the function of book study as a medium for Islamic legal literacy in Islamic boarding schools. In conclusion, the combination of the bandongan method with contextual discussions is effective in increasing the fiqh muamalah literacy of students and can be developed as a sustainable mentoring model.